A comparative study of laparoscopic versus mini laparotomy cholecystectomy - Naik, Suresh; Alam, Firoz; Yadav, Nagendra; Khandarpa, Akhil (International Surgery Journal, 2017)
Background: Gallstones are common in Indian population and its treatment has shown a decisive shift from open to minimally invasive route. There is no doubt that laparoscopy require longer and steeper learning curve and higher cost, especially in the absence of health insurance to majority of suburban and rural Indian population. However, preferences of patients are changing rapidly due to better level of awareness and availability of healthcare facility. Aims was to study safety and efficacy of laparoscopic cholecystectomy in patients of cholelithiasis by comparing with results of mini laparotomy cholecystectomy by comparing use of post-operative analgesia, operative Time, post-operative hospital stay, morbidity and mortality. Methods: It is a prospective randomized study of 100 Patients of cholelithiasis aged between 25 years to 65 years operated during 2016-2017 at Dr. D Y Patil medical college Pune. They were divided into mini laparotomy and laparoscopic cholecystectomy group by draw a lot method. Patient’s written valid informed consent for the particular procedure was taken and the pros and cons of both the procedure were explained in detail to the patient. This study was done after due clearance of ethical committee. Results: The median (range) operation time for laparoscopic cholecystectomy was 50-175 min (mean=103.98 min) and 35-95 min (mean=70 min) for mini laparotomy cholecystectomy (p<0.001). During the study period operation time for laparoscopic cholecystectomy showed a tendency to become shorter. The use of Injectable analgesics in case of laparoscopic cholecystectomy (Mean no. of days=1.5) is considerably less than mini laparotomy cholecystectomy (Mean no. of days=3.36). Conversion rate in literature in laparoscopic cholecystectomy ranges from 3% to 15% in well trained hands. In our series it is 6% in spite of being a teaching and training institution. Conclusions: Minimally invasive surgery is better than mini laparotomy cholecystectomy in terms of post-operative pain, analgesic requirement and early return to work. However, mini laparotomy cholecystectomy is preferred method for Surgeons in the beginning of their career and in case of difficult cholecystectomy.